A switching-type controller for wire rope tension coordination of electro-hydraulic-controlled double-rope winding hoisting systems. (November 2016) - Li, Xiang; Zhu, Zhen-Cai; Shen, Gang
An adaptive fuzzy sliding mode controller combining a sliding mode controller and an adaptive fuzzy controller is proposed to control the wire rope tension of a double-rope winding hoisting system in the presence of external disturbances and parameter uncertainties. The sliding mode controller is designed to yield a desired output signal for tension coordination control, and the adaptive fuzzy controller is employed to serialize the switching-type controller of the chattering because external disturbances are overwhelming. Stability of the overall closed-loop system under the adaptive fuzzy sliding mode controller is proved by Lyapunov theory. A three-variable feedback controller is employed to improve position tracking accuracy of hydraulic cylinders to ensure the tension coordination control performance. A double-rope winding hoisting simulation experimental system with xPC rapid prototyping technology is carried out to verify feasibility and effectiveness of the proposed adaptive fuzzy sliding mode controller. Simulation and experimental results demonstrate that the proposed controller yields a satisfactory wire rope tension coordination control performance on the double-rope winding hoisting experimental system compared to a traditional proportional–integral controller and the sliding mode controller.